A new jet fuel surrogate formulated by emulating the distribution of pyrolysis products obtained from shock tube experiments. (1st January 2021) - Yang, Ming; Lin, Shengqiang; Liao, Handong; Kang, Shiqing; Yang, Bin
Abstract: A new jet fuel surrogate is developed by emulating the distribution of pyrolysis products obtained from shock tube experiments. The distribution of pyrolysis products is described by the use of a series of pyrolysis curves, which refers to a graphical depiction of the concentrations of pyrolysis products plotted against temperatures. Besides, the matching on chemical properties of jet fuel, including molecular weight (MW), hydrogen/oxygen ratio (H/C ratio), derived cetane number (DCN), lower heating value (LHV) and threshold sooting index (TSI), is also taken into account during the formulation process. The new surrogate is a mixture of n - decane, iso -cetane and m -xylene, and these three components are selected through the simulation of pyrolytic process based on the consideration that their mixture can provide similar pyrolysis curves to the target fuel. The validity of the new surrogate has been evaluated extensively against available experimental results from homogeneous reaction systems and low dimensional premixed flames. Meanwhile, a definition of "Error function" is introduced to quantitatively analyze the agreement between calculated values by surrogate and measured data of Jet A. As a reference, the predictive capabilities of four surrogates published in the last ten years and one hybrid-chemistry model for jet fuel are also investigated under the same conditions. According to the simulated results, the new surrogate with a detailed chemical mechanism from CRECK Modeling group (Version 1412) is capable of presenting reasonable predictions on the major combustion behaviors of Jet A across a wide range of conditions, such as ignition delay time, laminar burning velocity and oxidative products distribution.